Effect of stock price informativeness on timing of share repurchases - Chee, Chong Meng; Ab Razak, Nazrul Hisyam (IRAJ International Journals, 2018)
A potential presence of managerial learning hypothesis (MLH) in market timing of share repurchases is addressed by finance literature in conjunction with some growing empirical evidences of MLH’s presence to some corporate finance decision. Despite numerous past researches focusing solely the managerial market timing, the researchers contend that the success of managerial market-timing in share repurchaseswould beattributed to the effect of private information conveyed in stock price (stock price informativeness).Research finding found evidence that managers learn private information from stock price to buy back their shares with more discount.Stock price informationess could be the tool for managers to improve their market timing skill to take advantage of stock market. The contributions of this research paper are to:identify research gaps in repurchase study;discuss effect of stock price informativeness on firm stock repurchase decision; and provide empirical finding to justify the presence of MLH.